Lecture guide in general inorganic chemistry : ADPCN-Compliant - Nucum, Zenaida T. (Quezon City, Philippines : C & E Publishing Inc., 2007)
Literacy in the sciences is a crucial component of any educational plan. Together with the humanities, it prepares the students to earn a living, be productive citizens, and live a full life enriched by continuous learning. Over and above becoming professionals, they also become useful members of the society of man.- - Preface.
Chapter 1. Significant figures and measurements -- Chapter 2. A short history of Science -- Chapter 3. Matter and the scopes of chemistry -- Chapter 4. Energy -- Chapter 5. The modern atomic theory -- Chapter 6. Nuclear energy and medical applications of radioactivity -- Chapter 7. The periodic table -- Chapter 8. Chemical bonding -- Chapter 9. Chemical kinetics and equilibrium -- Chapter 10. Oxidation reduction reactions -- Chapter 11. Stoichiometry -- Chapter 12. Stoichiometry in chemical reactions -- Chapter 13. States of matter and the effects of air pollution on the atmosphere -- Chapter 14. Oxygen, hydrogen, and water -- Chapter 15. Solutions -- Chapter 16. Acids, bases, and salts -- Chapter 17. Organic chemistry -- Chapter 18. Biomolecules -- Chapter 19. Medical machines -- Chapter 20. Diagnostic machines -- Chapter 21. Boron neutron capture theraphy.
Includes bibliographical references and index.
Keywords: CHEMISTRY, INORGANIC -- STUDY AND TEACHING (HIGHER)